Quantifying Sphagnum spp. presence and distribution along a gradient in aeolian mineral deposition in Icelandic mires - Lorenzo Vegliò 1996- (2024)
Aeolian dust deposition has been shown to affect natural ecosystems in different ways, for instance by increasing soil’s bulk density and mineral content, leading to shifts in vegetation. Due to Iceland frequent volcanic eruptions and vast sandy deserts and eroded areas, in combination with strong high-speed winds, considerable amounts of mineral and volcanic dusts get redistributed within Iceland’s territory. Mires are prone to dust accumulation because their waterlogged state easily captures windborne dust, leading to a buildup of dust particles, which results in Icelandic mires being minerotrophic and vascular plants dominated, rather than Sphagnum-dominated. As the dust gradient (Arnalds, 2010) goes from high deposition zones near dust sources to areas with very low deposition further afield, the following study investigated whether the gradual decrease in dust deposition along the gradient mirrors a gradual increase in Sphagnum presence rate as dust’s influence decrease. The study examined eleven mire sites along the dust deposition gradient by measuring Sphagnum presence rate and investigating how chemical (pH, EC, C/N ratio), physical (elevation, BD, LOI), and biological (species diversity and richness) factors relate to it in each site. Furthermore, Sphagnum species in each area were identified to assess variations at the species-level distribution. Contrary to the expected increase in Sphagnum presence rate with decreasing mineral deposition, findings reveal a complex, non-linear relationship between dust inputs and Sphagnum ecology. The results indicate high Sphagnum presence rate even in areas near dust sources and that certain Sphagnum species (e.g. S. teres, S. warnstorfii) exhibit adaptability to minerotrophic conditions, challenging traditional notions of Sphagnum's preference for oligotrophic environments. Individual environmental factors (e.g. pH, EC, BD) showed no statistical significance with Sphagnum presence rate when considered individually. However, a multivariate analysis incorporating ...